ENGLISH PRESERVICE TEACHERS' PERCEPTION OF ICT: THE STUDY ON THE STUDENTS FROM RURAL AREAS - Rais, Burhanudin; Kristiawan, Risto (English Review: Journal of English Education, 2022)
The development of technology brings a good effect on learning English. Some research supports that using technology in learning English increases students' comprehension. However, the fact in the field state that many teachers teach English using conventional methods without technology. On this basis, researchers aimed to examine the perceptions and attitudes of English preservice teachers. This research will be exciting because knowing the current perception of preservice teachers may impact their behavior with technology in the future. In conducting the study, the researchers used a descriptive qualitative method using interviews to obtain data. The criterion used is English education students who study at the higher education level in Sintang. There are 6 (six) students or preservice teachers that the researchers chose as the participants. The result of this research showed that all of the participants think that ICT is important for teaching English. Using ICT in learning can make students understand the material better, making them easier to find information from the material being taught.